[OA175] The european federation of medical physics algorithm for the evaluation of minimum staffing level of medical physics experts: Results of the italian experience. (August 2018) - Matheoud, Roberta; Menegotti, Loris; Strigari, Lidia
Abstract : Purpose: The evaluation of staffing level of Medical Physics Experts (MPE) in Medical Physics Departments (MPD) is a demanding need, especially in the light of the new European Directive 59–2013. An objective criterion to set the minimum staffing levels (MSL) for MPE is therefore needed. Methods: In April 2016 the European Federation for Medical Physics set the Policy Statement 7.1 on the role and responsibilities of MPE including criteria for evaluating MSL. This document indicates that the minimum staffing level of MPE should be 18/mil population, subdivided in 9, 2, 5 and 2/mil population for radiation therapy-RT, nuclear medicine-NM, radiology-RAD and radiation protection-RP specialties. A datasheet file (DF) for MPE MSL estimation was also provided. The Associazione Italiana di Fisica Medica (AIFM) in 2017 asked to Italian MPDs (160) the compilation of the DF. The Italian territory was divided into 16 areas roughly corresponding to regions/macro-regions. The collection of DF was scored as complete (100%), almost-complete (85–100%), partial (50–85%), poor ( < 50%) and null (0%), depending on the number of compiled DF with respect to the total DF distributed in that area. The data coming from complete and almost complete area collections were used to analyse the applicability of EFOMP algorithm, in terms of recommended MPE/mil (total and per sub-specialties). Results: 110 compiled DFs were collected (69 %). The collection of DF was complete, almost complete, partial and null in 3/16, 1/16, 7/16, 4/16 and 1/16 areas, respectively. By averaging the total MPE numbers estimated by EFOMP algorithm for the complete and almost complete areas, we obtained 26.6/mil (range 20.7–38.5/mil) while the actually MPE present were on average 13.4/mil (range 11.3–16.8/mil), indicating an actual overall need of MPE in these areas. The MPE estimated for sub-specialties were: 15.4, 3.0, 3.4 and 0.4 MPE/mil for RT, NM, DR and RP, respectively while the correspondent values recommended by EFOMP were 9.0, 2.0, 5.0 and 2.0. Conclusions: EFOMP algorithm provides an overestimation of total MPE of about 40% when compared with the recommendation of 18MPE/mil MSL. The estimated MPE for sub-specialties indicates an overestimation for RT and an underestimation for RP.